Use of stabilized compressed earth methodology for bricks manufacturing - Muñoz Perez, Socrates Pedro (2021)
Building materials such as concrete blocks and fired clay brick are very expensive and, in some circumstances, have a detrimental effect on the environment. Although there are some experiences and studies to improve the durability of bricks, these have not been sufficiently disseminated. One of the alternatives is stabilized compressed earth brick, as a sustainable material that uses locally available soils, combined with stabilizers to improve its resistance. Also, the construction development of these bricks is on-site and requires less qualified labor.